PENGARUH DEBT TO ASSET RATIO (DAR) DAN CURRENT RATIO (CR) TERHADAP RETURN ON EQUITY (ROE) PADA PT. ACE HARDWARE INDONESIA TBK PERIODE 2013 – 2022 - Alexsander Hutasoit; Agus Supriatna (Journal of Research and Publication Innovation, 2025)
This research aims to determine the effect of Debt to Asset Ratio and Current Ratio on Return on Equity partially or simultaneously at PT. Ace Hardware Indonesia Tbk from the 2013-2022 period. The independent variables used in the research are Debt to Asset Ratio and Current Ratio, while the dependent variable used is Return on Equity. This research method is descriptive quantitative. The population in this research is all financial reports of PT. Ace Hardware Indonesia Tbk 2013- 2022. With samples in the form of a consolidated financial position report and profit and loss statement. The analysis technique used is multiple linear regression and hypothesis testing using the t test to test partial relationships and the f test to test joint effects. Data analysis used SPSS version 26 software. The results of this research show that partially the Debt to Asset Ratio does not have a significant effect on Return on Equity. With the hypothesis test, the Tcount value was -0.430 < Ttable 2.364, this was also confirmed by the significant value of 0.680 > 0.05 . Partially, the Current Ratio has no effect on Return on Equity. By hypothesis testing, the Tcount value is 2.231 < Ttable 2.364 and is strengthened by a significant value of 0.601 > 0.05. And simultaneously, the Debt to Asset Ratio and current ratio on Return on Equity have no influence with the hypothesis test Tcount 2.489 < Ttable 4.46), this is also reinforced by the significance value of 0.153 > 0.05.